2021
DOI: 10.1096/fj.202100325rr
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin‐1 dependent regulation of polycystin‐2 via GRP94, a member of HSP90 family that resides in the endoplasmic reticulum

Abstract: Autosomal dominant polycystic kidney disease is a common inherited renal disorder that results from mutations in either PKD1 or PKD2, encoding polycystin-1 (PC1) and polycystin-2 (PC2), respectively. Downregulation or overexpression of PKD1 or PKD2 in mouse models results in renal cyst formation, suggesting that the quantity of PC1 and PC2 needs to be maintained within a tight functional window to prevent cystogenesis. Here we show that enhanced PC2 expression is a common feature of PKD1 mutant tissues, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Doxycycline treatment alone, without Pkd gene knockout had no effect on Glis2 expression. Pkd1 mutant primary cells also showed upregulation of Pkd2 transcripts, reproducing another feature of the in vivo TRAP RNASeq and published data 42 (Fig. 3d ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Doxycycline treatment alone, without Pkd gene knockout had no effect on Glis2 expression. Pkd1 mutant primary cells also showed upregulation of Pkd2 transcripts, reproducing another feature of the in vivo TRAP RNASeq and published data 42 (Fig. 3d ).…”
Section: Resultssupporting
confidence: 85%
“…The biological relevance of at least some elements of this gene set, which was selected without bias regarding functional roles, is supported by the inclusion of Pkd2 which is significantly upregulated 42 in response to inactivation of Pkd1 in vivo (Fig. 2a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the balance between PC1/PC2 might be important for correct cilia function to prevent polycystic disease. In this complex, PC2 is assumed to be available more abundant 2 and its expression was recently reported to be regulated by ER‐localized chaperones, 46 suggesting that impaired PC2 biosynthesis by decreased SEC61A1‐R236C expression might lead to the polycystic phenotypes observed in the patients described here.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, it was suggested that the amount of PC1 and PC2 should be within a certain tight range to prevent cystogenesis. Yao et al recently demonstrated that Pkd1- mutant mouse tissues exhibit increased expression of PC2, which is maintained by a new signaling axis involving histone deacetylase HDAC6 and GRP94 (a member of the HSP90 chaperone family) [ 86 ].…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciumentioning
confidence: 99%